2005
DOI: 10.1111/j.1341-8076.2005.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the role of folic acid, dietary folate intake and plasma folate concentration in Japan

Abstract: Information on the role of periconceptional intake of folic acid is not sufficiently disseminated to young women and health-care professionals alike. Pregnant women should be repeatedly recommended to take folic acid supplements of 400 microg/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Although this result is similar to what was found in the UAE (66.7 %) [16], other studies, such as Kondo and colleagues reported that less than 15 % of Japanese women were aware of a link between folic acid and NTDs [17]. In addition, a study in the United States revealed that 13 % of all women surveyed knew that folic acid helps prevent birth defects [18]; however, an UAE study reported lower rates, 69.7 % [16].…”
Section: Discussioncontrasting
confidence: 36%
“…Although this result is similar to what was found in the UAE (66.7 %) [16], other studies, such as Kondo and colleagues reported that less than 15 % of Japanese women were aware of a link between folic acid and NTDs [17]. In addition, a study in the United States revealed that 13 % of all women surveyed knew that folic acid helps prevent birth defects [18]; however, an UAE study reported lower rates, 69.7 % [16].…”
Section: Discussioncontrasting
confidence: 36%
“…Accordingly, there had not been fully investigated about folate intake and folate related biomarker in Japanese people. Recently, Kondo et al (2005) reported folate intake and serum folate concentration in pregnant Japanese women including all trimesters. However, there are no studies on folate intake and folate-related biomarkers including RBC folate concentration in pregnant Japanese woman in the first trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these intersectoral efforts, the proportion of supplement users in pregnant women has increased (20,21,24). As there are no current guidelines on whether or not to continue FA use after 12 wk gestation, there is concern among obstetricians and pregnant women.…”
Section: Discussionmentioning
confidence: 99%